Alternative Perspectives beyond the Perspectives: A Summary of Pauline Studies that has Nothing to Do with Piper or Wright - Worthington, Bruce (2013)
Given the overwhelming scholarly attention directed towards the Old and New Perspectives within the Pauline Studies guild, much worthwhile Pauline scholarship continues to float beneath or beyond our interpretive radar. Recent post-colonial, ecotheological and philosophical reappraisals of Paul are changing the way we do business—with some interesting alternative conclusions. As a ‘state of play’ synopsis, this article seeks to summarize ways in which alternative discourses like (1) continental philosophy, (2) ecological hermeneutics, (3) post-colonial/gender reconstructions, and (4) social-scientific theory can shed a necessary, nuanced light on Paul and his continued relevance beyond the duelling perspectives. However, I conclude by suggesting that most alternative ‘reconstructions’ significantly rely on the notion of early Christian egalitarian purity, and thus only confirm a modern liberal inclination to establish original, untainted, pure, Christian origins.
Keywords: Žižek; Post-colonial; Paul; Marxist; Ecological; Badiou